Keyword guessing on multi-user searchable encryption. (8th May 2019) - Li, Zhen; Zhao, Minghao; Jiang, Han; Xu, Qiuliang
Multi-user searchable encryption enables the client to perform keyword search over encrypted data while supporting authorisation management. Most of these schemes are constructed using public key encryption. However, public key encryption with keyword search is vulnerable to keyword guessing attack. Consequently, a secure channel is necessarily involved for secret information transformation, which leads to extra severe burden. This vulnerability is recognised in traditional searchable encryption, but it is still undecided whether it also exists in multi-user setting. In this paper, we firstly point out that keyword guessing attack is also a problem in multi-user searchable encryption without the supposed secure channel. By an in-depth investigation of some schemes proposed recently and simulating the keyword guessing attack on them, we present that none of these schemes can resist this attack. We make a comprehensive security definition and propose some open problems.